Pretreatment for Tunnel Karst Cave during Excavation: A Case Study of Guangxi, China - Junjie Li; Qiunan Chen; Xiaocheng Huang; Gen Zou; Jiazheng Deng (Advances in Civil Engineering)
Karst landscape is a general term for earth surfaces and underground patterns that have been formed by the dissolution of soluble rock. Karst landscapes are widely distributed throughout China—particularly in the Guangxi and Guangdong provinces. The main features of karst landscapes are typically reflected in karst caverns, sinkholes, and other geographical phenomena. During tunnel construction in karst areas, various forms of karst caverns may appear on the construction route, and they can cause hazards—such as water inrush and collapse—during tunnel construction. These hazards affect the tunnel construction process. As such, it is necessary to propose a treatment for karst caverns. In this work, a case study of the tunnels on the Hechi-Baise expressway is presented. A comprehensive pretreatment method suitable for this tunnel is proposed. On the premise of prioritizing the safety and timeline of construction, an optimized treatment scheme for the karst caverns of Hebai tunnel is followed. The optimized treatment scheme primarily includes calculation of safe thickness of tunnel face, strengthening the initial support and increasing the thickness of the second lining, increasing the reserved deformation, and grouting. The proposed scheme achieved favorable results in the treatment of a karst cavern in the Hebai tunnels.